Desafios da formação para o trabalho interprofissional no contexto da reabilitação - Bezerra, José Gutembergue de Vasconcelos (2017)
Interprofessional Work is an essential practice for integrality in health care by promoting integrated and collaborative actions among professionals from different areas focusing on the health needs of population. According to WHO (2010) Interprofessional Education occurs when two or more professions learn about the others, with the others and with each other for the effective collaboration and improvement of health outcomes. In view of this, this study sought to answer the following question: do the mandated supervised internships of a specialized rehabilitation center serve as an instrument for Interprofessional Health Training? It was then sought to understand the dynamics of health education through the preceptory from the principles of Interprofessional Education in the CER of UNCISAL, making the barriers and facilitators of this process visible and analyzing the pedagogical projects of physiotherapy, speech therapy and occupational therapy courses, for developing supervised internships in this center, from the perspective of interprofessionality. Using SPINK's Discursive Practices (2000) as a theoretical contribution, a qualitative, descriptive and exploratory approach was developed, whose tool for the production of information was the semi-structured interview. Through the dialogical maps of the senses produced, the following analytical categories were identified: conceptions about interprofessional education in health and interprofessionality; individual aspects facilitating or hindering interprofessional actions; the institution as promoter of work and interprofessional education in health. The pedagogical projects of the course analysis shows a consolidation of the proposal of the interprofessional training by orienting the design of the new curricular matrices of the courses focused on training sensitive to the collaborative practices. The research about interprofessionality in the context of rehabilitation found that its absence or its implementation is explained much more in the self-perception of the interest or resistance of each component over this work dynamics than in factors related to the interest of the other or the support of the management; signaling, therefore, that it is above all in the movement from the inside out, from the individual to the collective, that the changes can materialize in that direction. As a product of an intervention, a workshop was held with actors involved in raising awareness about the need for adoption and systematization of collaborative practices in the routine of the center, which would allow interprofessional experiences to the students, obeying what was defined by the pedagogical projects of the course. It is concluded, therefore, that the preceptory can assume the role of representing the bridge between interprofessional health education and the implementation of teamwork routines that lead to the systematic adoption of collaborative practices in the service.